Potential and importance of metalloproteinases and interleukins in inflammation and metastasization in non-small cell lung cancer - Pereira, João Luís; Gomes, Mónica; Teixeira, Ana Luísa; Coelho, Ana; Rolfo, Christian; Araújo, António (Translational Cancer Research, 2018)
It is now known that, in lung cancer, while there is a loss of the standard biomarkers, such as the EGFR or ALK rearrangements, there is also a loss of standard immune related biomarkers, such as the PD-1 and PD-L1. These findings resulted in new immunotherapies, already approved and which offer new options in the treatment of this cancer. Although the current overview is far better than decades ago, lung cancer continues to be the deadliest cancer of all. Thus, there is still a lack of biomarkers that can be used in order to revert that situation, whether through the finding of new therapeutic options or through the finding of new biomarkers which may help guide the treatment of the patient. Markers of inflammation and metastasization, such as metalloproteinases (MMPs) and its inhibitors or interleukins (ILs), may play that role as they are very important in carcinogenesis. In the cancer environment, MMPs and its inhibitors are often related to the inflammation, metastasis, angiogenesis and tumour growth. Their influence has a wide range and they can both promote or combat the development of cancer, although usually MMPs are related to bad prognosis and cancer development whereas its inhibitors are related to the opposite. Many of these have already been studied in the immune and tumour microenvironment, as is the case of MMP-2, MMP-7 or MMP-9, and the possibility for them to have a more critical role in this cancer is still being studied. Although the targeting of these biomolecules as a treatment option may not have the desired results, there is still room to study their importance in the prognosis and treatment response. As for ILs, these crucial components of the immune system response also have dual roles in lung cancer, since it is believed that not only they can enhance tumour cell recognition by effector cells, but also they can be used by the tumour in its microenvironment to edit, modulate and evade the immune system response. As it happens with the MMPs and its inhibitors, targeting these molecules or use them as therapy may not be the best option, but their potential role as prognostic biomarkers still stands.